Azo dye with nitrogen donor sets of atoms and its metal complexes: Synthesis, characterization, DFT, biological, anticancer and Molecular docking studies. (17th April 2018) - Mahmoud, Walaa H.; Sayed, Fatma N.; Mohamed, Gehad G.
Abstract : An azo derivative was synthesized by coupling diazotized 2, 6‐diaminopyridine with p‐dimethyl amino benzaldehyde and this new ligand formed a series of metal complexes with Cr(III), Mn(II), Fe(III), Co(II), Ni(II), Cu(II), Zn(II) and Cd(II) salts. These complexes were characterized on the basis of elemental analyses, molar conductance, infrared spectroscopy, UV–Vis, 1 H NMR, mass spectrometry, electronic spectra, magnetic susceptibility and ESR spectral studies, conductivity measurements, thermogravimetric analyses (TG‐DTG). The molecular and electronic structure of the azo ligand was optimized theoretically and the quantum chemical parameters were calculated. The ligand and its metal complexes were subjected to X‐ray powder diffraction study. The thermal stability of the ligand and its metal complexes was examined by thermogravimetry. The ligand and its complexes were tested for their in vitro antimicrobial activity, some of the complexes showed good antimicrobial activities against some selected bacterial and fungal strains. Anticancer activity of the ligand and its metal complexes are evaluated against human cancer (MCF‐7 cells viability). Molecular docking was used to predict the binding between azo ligand and the receptors of nucleoside diphosphate kinase of Staphylococcus aureus (3Q8U) and (3HB5) which is breast cancer mutant oxidoreductase. The docking study provided useful structural information for inhibition studies. Abstract : The interaction between L and protein receptor 3Q8U. New azodye ligand and its binary transition metal complexes were prepared. The bonding and stereochemistry were deduced from elemental and spectroscopic data. The activation thermodynamic parameters are calculated using DTG curves. The quantum chemical parameters were calculated using DFT method. The metal complexes showed antimicrobial inhibition capacity much more than parent azodye ligand. Their anticancer evaluation against standard tumor cell lines (MCF7) was performed. The molecular docking study were performed with different proteins.